PSYCHOLOGICAL PRINCIPLES OF BULLYING AT JUVENILE AGE - Onufriieva, Liana; Honcharuk, Nataliia (PSYCHOLOGICAL JOURNAL, 2019)
The article deals with the problem of bullying among the senior pupils. The urgency of the problem is confirmed by statistical data, because today Ukraine is on the 4th place in Europe with regard to the propagation of the problem of bullying. At schools 45.3% of children were victims of bullying and 42.2% of children provoked it themselves, testifying that the problem of the bullying is important and relevant. The approaches to explain this phenomenon are described by the authors as a psychological phenomenon. The forms and types of bullying are singled out. The main features of bullying as a system concept, covering psychological, physical and other types of directed aggressive influence are revealed. During the empirical study, characteristics have been identified that make it possible to study the various aspects of the psychological problem in question. In particular, the information-content and structural-positional aspects of it were worked out and the necessity of developing a differentiated approach to overcoming bullying as a diversified form of child abuse was proved. According to the results of the research, the attention is focused at the most urgent issues, which are the task of enhanced psychological and pedagogical control over the behavior and conditions of schoolchildren development, the formation of skills of constructive communication among peers and child-parent interaction in crisis situations. The experience of effective communication demonstrates that the support of other significant people is needed for each crisis situation. It is revealed that in the situation of bullying where the child suffers from destructive influence, adults and peers should not only realize that the child needs a help, but they also should be able to provide it really. At the same time, the results of the survey state that this support is not always available. It is shown that the critical point in this situation is that children almost do not receive protection from teachers who should first of all help them as victims of bullying because they are constantly in contact with children and should notice such cases. The detailed analysis shows that schoolchildren haven’t developed skills of constructive interaction and ability to react in crisis situations. Based on the fact that these skills are not formed on their own, and in Ukrainian schools there are no disciplines in the psychology of communication, it should be advisable to add to the school curriculum a compulsory course aimed at the formation of communicative skills in various spheres of life and activities relating to communication with peers, business communication with teachers and other adults, family communication in the family, as well as constructive skills to build communication in crisis situations, using ethical norms of interaction.